Координатно-чувствительный фотоэлектромагнитный детектор ИК-излучения на основе HgCdTe - Bodnaruk, O. A.; Gromko, E. D.; Markov, A. V.; Ostapov, S. E.; Rarenko, I. M.; Shvets, A. G. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
A design of a coordinate-sensitive IR detector based on HgCdTe, operating in the mid-infrared spectral range and utilizing the photoelectromagnetic effect, is presented. A detailed analysis of its design and main parameters is carried out.